A Systematic Review and Metanalysis on the Use of Hermetia illucens and Tenebrio molitor in Diets for Poultry - Yuri Katagiri Dalmoro; Carolina H. Franceschi; Catarina Stefanello (Veterinary Sciences, 2023)
Insect meal as a protein source has been considered a sustainable way to feed animals. H. illucens and T. molitor larvae meal are considered high-protein sources for poultry, also presenting considerable amounts of fatty acids, vitamins, and minerals. However, other potential components in insect meal and insect oil have been more extensively studied in recent years. Chitin, lauric acid, and antimicrobial peptides can present antimicrobial and prebiotic functions, indicating that low levels of their inclusion in insect meal can beneficially affect broilers’ health and immune responses. This systematic review was developed to study the impact of insect products on the health parameters of broilers, and a metanalysis was conducted to evaluate the effects on performance. A database was obtained based on a selection of manuscripts from January 2016 to January 2023, following the mentioned parameters. Both H. illucens and T. molitor meal or oil products had positive effects on poultry health status, especially on the ileal and cecal microbiota population, immune responses, and antimicrobial properties. The average daily gain was greater in broilers fed T. molitor meal compared to H. illucens meal (p = 0.002). The results suggest that low levels of insect meal are suitable for broilers, without resulting in negative effects on body weight gain and the feed conversion ratio, while the insect oil can totally replace soybean oil without negative impacts.